Analisis Peran Relawan TIK dalam Penguatan Literasi Digital Masyarakat - Rina Fitriani; Siti Chodijah; Aidah Hami; Diand Mardiana (Puslitbang Akademi Relawan TIK Indonesia, 2025)
The development of the industrial revolution has brought human’s civilization in applying ICT (Information and Communication Technology) massively. The Indonesian government is trying to achieve “Indonesia Connected”. Unfortunately many Indonesian citizens don't have any access and enough knowledge about ICT itself. The research project presents a solution for the problem above. We hope the research project will be able to give a great description about how ICT-Volunteer helps people socializing digital literacy and helps people to access TIK in Indonesia. The research project uses the approach “perfective system”. The definition of perspective system is a study on a system by questioning: how and why the system can work properly. The researcher will enter the system doing an observation figuring out how ICT-volunteers of Indonesia work doing their volunteering job. Many activities have been done by Bapak Bambang Soeprijanto as the director of informatics empowerment since 2008. He has made some meetings, collaboration and coordination among stakeholders in building Indonesian informatics society. (relawantik.or.id, n.d.). The director of informatics empowerment, Ibu Mariam F. Barata, in 2011 continued the policy by supporting bigger meetings such as communication forum, coordination, collaboration and an event “Kerjasama Komunitas TIK“ (FK5T) national level. That event also established an organization, Relawan TIK on July 4th, 2011. It was witnessed by the General Director of Informatics Application. Kemkominfo, Ashwin Sasongko. It was decided as the anniversary of Relawan TIK Indonesia. (Indonesian ICT-volunteer). Being a member of Relawan TIK has many benefits such as an opportunity of sharing knowledge and skill of ICT, improving communication and leadership skill, building networking and positive social relationship.